Automated multi-plug filtration cleanup method for analysis of 48 pesticide residues in green tea using liquid chromatography-tandem mass spectrometry. (January 2022) - Song, Le; Zeng, Wenbo; Li, An; Pan, Canping; Pan, Ligang
Abstract: An automated multi-plug filtration cleanup (m-PFC) method, based on QuEChERS extraction was developed for the analysis of 48 pesticides in green tea. The carboxyl functionalized multi-walled carbon nanotubes (MWCNTs-COOH) were firstly packed in m-PFC columns and functioned as promising sorbents with better clean-up capability. The different parameters of automated m-PFC equipment and extraction conditions were optimized. The automated method integrated cleanup and filtration (through filter membrane) procedure into a single run before injected to the detection instrument. Comparison to d-SPE and manual m-PFC method, the automated method could handle a batch of samples simultaneously with better purification effect. Acceptable recoveries at three concentration levels from 71% to 114% were obtained (except carbendazim and bifenazate) with relative standard deviations lower than 18%. The proposed automated m-PFC method offered a great compromise between rapidity, convenience and efficiency. It was successfully applied for market monitoring of pesticide residues with robust analyze data. Highlights: Automated m-PFC method for analysis of 48 pesticides in green tea. Functionalized MWCNTs were mixed with other sorbents to assess cleanup performance. Extraction and automated m-PFC process were optimized by recovery and matrix effect. Method validation showed superior purification efficiency and robust analysis data. The automated method can handle a batch of real sample in routine pesticide analysis.